2007
DOI: 10.1007/s00442-006-0642-6
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural versus physiological mediation of life history under predation risk

Abstract: Predator-generated variation in prey energy intake remains the dominant explanation of adaptive response to predation risk in prey life history, morphology and physiology across a wide range of taxa. This "behavioural hypothesis" suggest that chemical or visual signals of predation risk reduce prey energy intake leading to a life history characterized by a small size and late age at maturity. However, size-selective predation can induce either smaller size-early age or large size-late age life history. The alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
130
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 48 publications
5
130
1
2
Order By: Relevance
“…This kind of plastic change may be a by-product of anti-predator behaviour (Ball & Baker, 1996) or represent adaptive modifications of growth schedules per se (Beckerman et al, 2007). Within this conceptual framework, the case of E. atomaria can be considered an adaptive modification, as both growth rate and development rate are affected (see also Tammaru et al, 2000, for a related discussion of crowding effects).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of plastic change may be a by-product of anti-predator behaviour (Ball & Baker, 1996) or represent adaptive modifications of growth schedules per se (Beckerman et al, 2007). Within this conceptual framework, the case of E. atomaria can be considered an adaptive modification, as both growth rate and development rate are affected (see also Tammaru et al, 2000, for a related discussion of crowding effects).…”
Section: Discussionmentioning
confidence: 99%
“…Predation is another factor commonly recognized as modelling the maximum size and size at maturity of many species (Alon and Stancyk 1982, Reznick and Endler 1982, Beckerman et al 2007) and it could be responsible for the observed differences. However, no information is available about predation pressure on P. macrodactylus at any of the localities.…”
Section: Discussionmentioning
confidence: 99%
“…Our result is more in concordance with a general initial response to a disturbance, which may or may not include predation threat. In terms of metabolism, the general initial response to a disturbance is an increase in oxygen consumption from elevated respiration (Woodley & Peterson 2003, Beckerman et al 2007). Thus, we suggest that in this short-term response, the increase in the vigilance response pays off for any disturbance, threat or benign.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, induction of stress proteins has been demonstrated under the risk of predation in a variety of species (Kagawa et al 1999 Pauwels et al 2007, Slos & Stocks 2008. As a response to increased need for stress proteins, an increase of energy consumption has also been observed (Woodley & Peterson 2003, Beckerman et al 2007, Slos & Stocks 2008, which in turn could be linked to predator-induced growth reduction (Slos & Stocks 2008).…”
Section: Introductionmentioning
confidence: 99%